The symbolical meaning of Macanan dance in Barongan Blora - Budy, Elinta (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
This study is aiming at finding out the symbolical meaning of Macanan dance in Barongan Blora. The method implied in the study was qualitative with ethnochoreology approach. Results indicated that Macanan dance is a typical dance immitating the movement of an animal which is a tiger, which is known also in Indonesia as ‘macan’. It also illustrates some movements which resemble the activity of a group of farmers. This study concluded that the movement of Macanan dance contained specific meanings; specifically representing and illustrating the life of Blora Regency’s agricultural community in Indonesia.